Execution of State Seized Property Based on Corruption Conviction Court Decisions Later Burdened with Bank Liens - Abvianto Syaifullah; Didik Endro Purwoleksono; Taufik Rachman (Faculty of Law, Universitas Pekalongan, 2023)
One of the elements in the crime of corruption is the loss of state finances or the state economy, so that this element is the background for the formation of legislation regarding corruption crimes, both the old regulation, namely Law Number 3 of 1971 and the new regulation, namely Law Number 31 of 1999 concerning Eradication of Corruption Crimes as amended by Law Number 20 of 2001 concerning Amendments to Law Number 31 of 1999 concerning Eradication of Corruption Crimes which establishes a policy that state financial losses must be returned or replaced by the perpetrators of corruption (asset recovery). When the goods confiscated by the state are free or not encumbered by property guarantees, they can be directly executed by the Prosecutor in accordance with statutory provisions, but legal problems occur when the assets confiscated by the state turn out to be later encumbered by Mortgage Rights by the Bank/creditor after a court decision which in its verdict is